A bend-resistant data line sheath and a method of making the same

CN122958867APending Publication Date: 2026-10-23DONGGUAN YUYANG ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610906242.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

上述两种方案虽然在抑制弯折形变方面产生了积极效果,但均伴随着护套柔性的下降,宏观硬度增加,手感变硬

Benefits of technology

本发明通过向液体硅橡胶基体中引入一种梳型聚硅氧烷-聚乙二醇嵌段共聚物作为弯折稳定剂。该弯折稳定剂的分子以聚硅氧烷为主链,主链两侧通过化学键均匀接枝有聚乙二醇侧链,并且有二乙烯基二氯硅烷嵌段作为活性反应位点,引入的聚乙二醇侧链排列规整,形成了均匀梳型嵌段结构,其作用机理为:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to a kind of bending-resistant data line sheath and preparation method thereof, belong to silicone rubber material technical field.The sheath is mixed by liquid silicone rubber, bending stabilizer and additive and is formed by injection vulcanization, the bending stabilizer is prepared by two-step method: first, terminal hydroxyl silicone oil and divinyl dichlorosilane substitution reaction occurs, and alkenyl polyorganosiloxane intermediate is obtained, then the intermediate and polyethylene glycol monomethyl ether thiol occur under the initiation of ultraviolet light mercapto-alkene click addition reaction, and comb-type polysiloxane-polyethylene glycol block copolymer is prepared;The polysiloxane main chain of the bending stabilizer is compatible with silicone rubber matrix, and the polyethylene glycol side chain forms uniformly distributed physical entanglement in the matrix due to the difference in compatibility, constructs topological constraint system, cooperatively inhibits silicone rubber molecular chain slip under bending stress, and can dissipate stress by conformation adjustment, thereby significantly improve the anti-bending deformation and recovery ability under the premise of maintaining the flexibility of sheath.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of silicone rubber material technology, specifically, it relates to a bend-resistant data cable sheath and its preparation method. Background Technology

[0002] As a key component for connecting electronic devices and facilitating data exchange, the performance and lifespan of data cables directly impact the user experience. During frequent use, scenarios such as plugging and unplugging, storage, and winding subject data cables to repeated bending stress, requiring excellent flexibility and resistance to repeated bending damage. Among current data cable sheath materials, silicone rubber exhibits significant advantages due to its unique chemical structure. The main chain of silicone rubber is composed of alternating silicon-oxygen bonds, exhibiting excellent flexibility and resilience on a macroscopic scale. Simultaneously, silicone rubber possesses excellent high and low temperature resistance, resistance to yellowing, and good biocompatibility, containing no harmful plasticizers and being non-irritating to the skin. Therefore, silicone rubber has been widely used in the field of high-end data cable sheaths.

[0003] Research has revealed that the main modes of bending failure in silicone rubber sheaths are bending relaxation and deformation accumulation. Specifically, after undergoing numerous bending cycles, the sheath gradually experiences irreversible loosening deformation, leading to separation and relative slippage from the internal conductor. This results in gaps between the sheath layer and the conductor, affecting the overall stability of the conductor structure and ultimately causing crack propagation failure under continuous bending. The underlying cause is that the interaction forces between silicone rubber molecular chains essentially rely on the van der Waals forces between the methyl side groups. These forces are relatively weak, and under long-term external stress, relative slippage occurs between the molecular chains. The slipped molecular conformation cannot be fully restored, leading to irreversible structural relaxation of the cross-linked network. This ultimately manifests as macroscopic loosening deformation and dimensional instability in the sheath, and even bending cracking failure, affecting both the protective and aesthetic properties of the sheath.

[0004] To address the aforementioned issues, existing technologies primarily modify silicone rubber through two approaches: physical strengthening and chemical crosslinking. Physical strengthening involves adding reinforcing fillers (such as fumed silica, nano-silica, and carbon nanotubes) to the silicone rubber matrix. By controlling the chemical environment on the filler surface, hydrogen bonds or van der Waals forces are formed between the filler and the silicone rubber molecular chains, thereby enhancing the system's cohesion and inhibiting chain slippage under stress. Chemical crosslinking, on the other hand, involves optimizing the type and amount of crosslinking agents in the vulcanization system to increase the density of the silicone rubber crosslinking network, thus reducing the mobility of the molecular chains under stress. While both methods have shown positive effects in suppressing bending deformation, they are both accompanied by a decrease in sheath flexibility, an increase in macroscopic hardness, and a harder feel. Summary of the Invention

[0005] In order to solve the technical problems mentioned in the background art, the purpose of this invention is to provide a bend-resistant data cable sheath and its preparation method.

[0006] The objective of this invention can be achieved through the following technical solutions: A bend-resistant data cable sheath is made of liquid silicone rubber, bend stabilizer and additives mixed and injection vulcanized.

[0007] The bending stabilizer is prepared by the following steps: Step A1: Under a dry atmosphere, hydroxyl-terminated silicone oil is mixed in anhydrous tetrahydrofuran. After cooling in an ice-water bath, divinyldichlorosilane is slowly added. Then, the ice-water bath is removed and triethylamine is added to carry out a substitution reaction. After the reaction is complete, the mixture is filtered and the tetrahydrofuran is recovered by rotary evaporation to obtain an alkenylated polysiloxane intermediate. Step A2: Dissolve benzoin dimethyl ether in acetone, then add alkenylated polysiloxane intermediate and polyethylene glycol monomethyl ether mercapto under nitrogen protection and mix well. Carry out the addition reaction under ultraviolet irradiation at room temperature. After the reaction is complete, rotary evaporate to recover acetone. Wash the substrate with deionized water and dry to obtain the bending stabilizer.

[0008] Furthermore, the molar ratio of the hydroxyl content of divinyldichlorosilane and hydroxyl-terminated silicone oil is 1:2.2-2.4, and the amount of triethylamine used is 10-18 wt% of the weight of both. The hydroxyl groups at the end of the hydroxyl-terminated silicone oil undergo a substitution reaction with divinyldichlorosilane, introducing vinyl groups into the intermediate molecule as active sites for subsequent click reactions, while simultaneously achieving the orderly extension of polysiloxane segments.

[0009] Preferably, the average molecular weight of the hydroxyl-terminated silicone oil is 2000-3000. With this molecular weight, the polysiloxane segmental block structure provides a better overall improvement in the mechanical properties and bending stability of the sheath.

[0010] Furthermore, the molar ratio of thiol groups in the vinyl group of the alkenylated polysiloxane intermediate to the thiol group of polyethylene glycol monomethyl ether is 1:1.05-1.1, and the benzoin dimethyl ether accounts for 0.05-0.07 wt% of the total amount of both. The thiol group at the thiol end of the polyethylene glycol monomethyl ether undergoes a thiol-alkene click addition reaction with the vinyl group on the side chain of the alkenylated polysiloxane intermediate under ultraviolet light initiation to form a thioether bond, thereby covalently grafting the polyethylene glycol side chain onto the polysiloxane backbone to form a comb-shaped polymer. Preferably, the average molecular weight of the polyethylene glycol monomethyl ether thiol group is 500-1000. The side chain at this molecular weight forms a uniform comb-like structure with the main chain constructed from the alkenylated polysiloxane intermediate, and forms appropriate spatial coiling and entanglement in the silicone rubber matrix, effectively improving bending stability.

[0011] Preferably, the ultraviolet irradiation intensity is 25-35 mW / cm². 2At this intensity, the click addition reaction of mercapto-olefins has a high grafting rate, making it easy to form uniform grafts, which has a better effect on improving the stability of bending resistance.

[0012] Preferably, the bending stabilizer accounts for 5.5-9.2 wt% of the sheath components, giving the sheath good bending resistance while maintaining good overall mechanical properties.

[0013] Among them, the additives include mold release agents used for processing and molding, and functional additives that impart properties such as mildew prevention and antistatic agents. The amount added should be adjusted as needed, and the total amount added should not exceed 2.0 wt%.

[0014] The preparation method of this bend-resistant data cable sheath is as follows: the components are mixed evenly, and the mixture is sequentially injection molded, demolded, and vulcanized to obtain the bend-resistant data cable sheath.

[0015] Preferably, the injection molding temperature is 160-170℃, the injection pressure is 40-45MPa, and the vulcanization molding temperature is 200-220℃.

[0016] The beneficial effects of this invention are: This invention introduces a comb-shaped polysiloxane-polyethylene glycol block copolymer as a flexural stabilizer into a liquid silicone rubber matrix. The flexural stabilizer has a polysiloxane main chain, with polyethylene glycol side chains uniformly grafted onto both sides of the main chain via chemical bonds. Divinyldichlorosilane blocks serve as active reaction sites. The introduced polyethylene glycol side chains are regularly arranged, forming a uniform comb-shaped block structure. Its mechanism of action is as follows: The polysiloxane backbone of the bending stabilizer has the same chemical structure as the silicone rubber matrix, and the two have good thermodynamic compatibility. However, the polyethylene glycol (PEG) side chain segments have relatively low compatibility with the silicone rubber matrix. This compatibility difference drives the PEG side chains to form tight physical entanglements in local areas. These entanglements are dispersed in the silicone rubber crosslinking network, constructing a multi-point topological constraint system at the molecular level. When the sheath is subjected to external bending stress, these uniformly distributed physical entanglements can synergistically inhibit the relative slippage of the silicone rubber molecular chains, thereby effectively mitigating the loose deformation and dimensional instability of the sheath during long-term repeated bending. When the stress is relieved, the PEG side chains, with their inherent entropic elasticity and spatial conformation recovery ability, can drive the constrained silicone rubber molecular chains to return to their initial state, giving the sheath excellent deformation recovery performance.

[0017] Compared to existing technologies that suppress molecular chain slippage by increasing crosslinking density or adding large amounts of filler, the topological constraint mechanism of this invention is a non-covalent physical entanglement. This mechanism does not change the essential structure of the silicone rubber backbone, nor does it significantly increase the crosslinking density or filler volume fraction of the system. Therefore, it does not significantly lead to problems such as increased sheath hardness, decreased elongation at break, or a stiffer feel, resulting in a loss of flexibility. During bending, the polyethylene glycol side chains can dissipate some of the external stress through conformational adjustments (such as chain segment compression, torsion, and rearrangement), thereby enabling the sheath to achieve significantly better bending resistance than traditional methods while maintaining the inherent flexibility of silicone rubber. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1: Preparation of a bend-resistant data cable sheath. The specific implementation process is as follows: 1) Preparation of bending stabilizer Step A1: Continuously purge dry air into the reactor to remove moisture. Add hydroxyl-terminated silicone oil and anhydrous tetrahydrofuran, stirring and mixing. Cool the reaction system to 5°C using an ice-water bath. Slowly add divinyldichlorosilane, controlling the reaction system temperature to not exceed 10°C during the addition process. After complete addition, remove the ice-water bath and simultaneously add triethylamine, continuing stirring for 4 hours. In the reaction, the hydroxyl-terminated silicone oil is MY2030-20, with an average molecular weight of 2000 and a hydroxyl content of 1.7%. The molar ratio of hydroxyl content of divinyldichlorosilane to hydroxyl-terminated silicone oil is 1:2.2. The amount of triethylamine used is 10 wt% of the total weight of both, and the amount of anhydrous tetrahydrofuran used is 50 wt% of the total weight of both. After the reaction is complete, filter to remove salts, and rotary evaporate to recover tetrahydrofuran, thus producing the alkenylated polysiloxane intermediate.

[0020] Step A2: Mix benzoin dimethyl ether and acetone, then purge with nitrogen for protection. Add alkenylated polysiloxane intermediate and polyethylene glycol monomethyl ether mercaptoyl group, and mix thoroughly. Apply a 365nm ultraviolet light source at room temperature with an intensity of 25mW / cm². 2The reaction was subjected to ultraviolet irradiation for 2.5 hours. The polyethylene glycol monomethyl ether mercapto group was model mPEG-SH-550 with an average molecular weight of 550. The molar ratio of the vinyl groups in the alkenylated polysiloxane intermediate to the mercapto groups in the polyethylene glycol monomethyl ether mercapto group was controlled at 1:1.05. Benzoin dimethyl ether accounted for 0.07 wt% of the total amount of both. Acetone was used at 1.2 times the total weight of both. After the reaction was complete, the acetone was recovered by rotary evaporation. The substrate was washed with deionized water and dried to obtain the bending stabilizer.

[0021] 2) Preparation of the bend-resistant data cable sheath Metered components: 5.5 wt% flexural stabilizer, prepared in this embodiment; 1.0 wt% release agent, model MSKMD886; 0.07 wt% antifungal agent, model JLZ-4; balance is liquid silicone rubber, model ELASTOSIL® LR 3003 / 30A / B.

[0022] Curing and molding: Mix the raw materials of each component, degas them under vacuum, and inject them into the data cable sheath mold. Control the temperature at 170℃, the injection pressure at 45MPa, and hold the pressure for 180s. The tubular blank is formed by injection molding. After demolding, it is transferred to a vulcanizing kettle and vulcanized at 220℃ for 3.5h. The sheath is obtained after vulcanization molding.

[0023] Example 2: Preparation of a bend-resistant data cable sheath. The specific implementation process is as follows: 1) Preparation of bending stabilizer Step A1: Continuously purge dry air into the reactor to remove moisture. Add hydroxyl-terminated silicone oil and anhydrous tetrahydrofuran, stirring and mixing. Cool the reaction system to 5°C using an ice-water bath. Slowly add divinyldichlorosilane, controlling the reaction system temperature to not exceed 10°C during the addition process. After complete addition, remove the ice-water bath and simultaneously add triethylamine, continuing stirring for 6 hours. In the reaction, the hydroxyl-terminated silicone oil is MY2030-30, with an average molecular weight of 3000 and a hydroxyl content of 1.1%. The molar ratio of hydroxyl content of divinyldichlorosilane to hydroxyl-terminated silicone oil is 1:2.4. The amount of triethylamine used is 18 wt% of the total weight of both, and the amount of anhydrous tetrahydrofuran used is 85 wt% of the total weight of both. After the reaction is complete, filter to remove salts, and rotary evaporate to recover tetrahydrofuran, thus producing the alkenylated polysiloxane intermediate.

[0024] Step A2: Mix benzoin dimethyl ether and acetone, then purge with nitrogen for protection. Add the alkenylated polysiloxane intermediate and polyethylene glycol monomethyl ether mercapto and mix thoroughly. Apply a 365nm ultraviolet light source at room temperature with an intensity of 35mW / cm². 2The reaction was subjected to ultraviolet irradiation for 4 hours. The polyethylene glycol monomethyl ether mercapto group was model mPEG-SH-750 with an average molecular weight of 750. The molar ratio of the vinyl groups in the alkenylated polysiloxane intermediate to the mercapto groups in the polyethylene glycol monomethyl ether was controlled at 1:1.1. Benzoin dimethyl ether accounted for 0.05 wt% of the total amount of both, and acetone was used at 1.6 times the total weight of both. After the reaction was complete, the acetone was recovered by rotary evaporation, the substrate was washed with deionized water, and dried to obtain the bending stabilizer.

[0025] 2) Preparation of the bend-resistant data cable sheath Metered components: 9.2 wt% flexural stabilizer, prepared in this embodiment; 0.8 wt% release agent, model MSKMD886; 0.05 wt% antifungal agent, model JLZ-4; balance is liquid silicone rubber, model ELASTOSIL® LR 3003 / 30A / B.

[0026] Curing and molding: Mix the raw materials of each component, degas them under vacuum, and inject them into the data cable sheath mold. Control the temperature at 160℃, the injection pressure at 40MPa, and hold the pressure for 220s. The tubular blank is formed by injection molding. After demolding, it is transferred to a vulcanizing kettle and vulcanized at 200℃ for 4 hours. The sheath is obtained after vulcanization molding.

[0027] Example 3: Preparation of a bend-resistant data cable sheath. The specific implementation process is as follows: 1) Preparation of bending stabilizer Step A1: Continuously purge dry air into the reactor to remove moisture. Add hydroxyl-terminated silicone oil and anhydrous tetrahydrofuran, stirring and mixing. Cool the reaction system to 5°C using an ice-water bath. Slowly add divinyldichlorosilane, controlling the reaction system temperature to not exceed 10°C during the addition process. After complete addition, remove the ice-water bath and simultaneously add triethylamine, continuing stirring for 4.5 hours. In the reaction, the hydroxyl-terminated silicone oil is MY2030-20, with an average molecular weight of 2000 and a hydroxyl content of 1.7%. The molar ratio of hydroxyl content of divinyldichlorosilane to hydroxyl-terminated silicone oil is 1:2.2. The amount of triethylamine used is 15 wt% of the total weight of both, and the amount of anhydrous tetrahydrofuran used is 60 wt% of the total weight of both. After the reaction is complete, filter to remove salts, and recover tetrahydrofuran by rotary evaporation to obtain the alkenylated polysiloxane intermediate.

[0028] Step A2: Mix benzoin dimethyl ether and acetone, then purge with nitrogen for protection. Add alkenylated polysiloxane intermediate and polyethylene glycol monomethyl ether mercaptoyl group, and mix thoroughly. Apply a 365nm ultraviolet light source at room temperature with an intensity of 30mW / cm². 2The reaction was subjected to ultraviolet irradiation for 3.2 hours. The polyethylene glycol monomethyl ether mercapto group was model mPEG-SH-750 with an average molecular weight of 750. The molar ratio of the vinyl groups in the alkenylated polysiloxane intermediate to the mercapto groups in the polyethylene glycol monomethyl ether mercapto group was controlled at 1:1.08. Benzoin dimethyl ether accounted for 0.06 wt% of the total amount of both. Acetone was used at 1.5 times the total weight of both. After the reaction was complete, the acetone was recovered by rotary evaporation. The substrate was washed with deionized water and dried to obtain the bending stabilizer.

[0029] 2) Preparation of the bend-resistant data cable sheath Metered components: 8.0 wt% flexural stabilizer, prepared in this embodiment; 0.9 wt% release agent, model MSKMD886; 0.06 wt% antifungal agent, model JLZ-4; balance is liquid silicone rubber, model ELASTOSIL® LR 3003 / 30A / B.

[0030] Curing and molding: Mix the raw materials of each component, degas them under vacuum, and inject them into the data cable sheath mold. Control the temperature at 170℃, the injection pressure at 42MPa, and hold the pressure for 200s. The tubular blank is formed by injection molding. After demolding, it is transferred to a vulcanizing kettle and vulcanized at 200℃ for 4 hours. The sheath is obtained after vulcanization molding.

[0031] Comparative Example 1 was set as a blank control. The specific implementation process was the same as in Example 3. No bending stabilizer was added to the components used to prepare the sheath. The balance was supplemented by liquid silicone rubber. The rest were the same.

[0032] Comparative Example 2, following the implementation method of Example 3, replaced the bending stabilizer with an equal amount of AEROSIL R974 oleophilic modified fumed silica, with the rest remaining the same.

[0033] Comparative Example 3 was carried out in accordance with the method of Example 3, but without adding a bending stabilizer, 4 wt% of XHG-202-2410 crosslinking agent was added, with the balance supplemented by liquid silicone rubber, and the rest were the same.

[0034] Mechanical performance tests were conducted on the above sheaths, specifically including: tensile performance testing according to GB / T 528-2009 standard; tear performance testing according to GB / T 529-2008 standard; and Shore A hardness testing according to GB / T 531.1-2008 standard. The specific test results are shown in Table 1. Table 1 Mechanical performance test results

[0035] As shown in Table 1 above, the data from Example 3 and Comparative Examples 1-3 were compared and analyzed. The mechanical properties of each sample were similar. Among them, the tensile strength of Example 3, Comparative Examples 2 and 3 increased slightly compared with the blank control of Comparative Example 1, while the elongation decreased to a certain extent. This indicates that a certain degree of strengthening effect occurred in Example 3, which is related to the strengthening formed by the comb-shaped structure of the bending stabilizer. In terms of tear resistance, Example 3 showed a more significant improvement. It is believed that this is related to the strengthening of the side chain of the bending stabilizer molecule and the energy consumption of conformational change. In summary, the sheath material prepared in this example maintained good comprehensive strength and toughness performance.

[0036] The above sheaths were subjected to bending resistance tests, specifically including: bending life test, i.e., with a bending radius of 5mm, bending angle ±90°, bending rate of 30 times / min, the number of bends at which visible cracks appeared was recorded as the bending life; the energy storage modulus after 5000, 10000, and 15000 bends was measured, and the bending fatigue modulus decay rate ΔE was calculated by comparing it with the initial energy storage modulus, ΔE = (initial energy storage modulus - energy storage modulus after bending) / initial energy storage modulus × 100%, and recorded as ΔE1, ΔE2, and ΔE3 respectively. The specific test results are shown in Table 2: Table 2 Results of flexural resistance test

[0037] As can be seen from the test data in Table 2, the bending life of Example 3 is significantly improved compared to the comparative example, demonstrating excellent bending resistance. Furthermore, considering the decrease in storage modulus during the bending process, Comparative Example 2, which is reinforced with filler, showed a significant decrease in storage modulus after 5000 bends, possibly related to the debonding of the filler from the silicone rubber matrix, leading to sheath deformation. Comparative Example 3, which is reinforced with crosslinking, showed a slight improvement in bending life compared to Comparative Example 1, but still experienced a significant decrease in storage modulus after 5000 bends. This may be due to irreversible molecular chain relaxation formed during the bending process in the crosslinked structure.

[0038] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0039] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A bend-resistant data cable sheath, characterized in that, It is made by mixing liquid silicone rubber, flexural stabilizer and additives and then molding by injection vulcanization; The bending stabilizer is prepared by the following steps: Step A1: Under a dry atmosphere, hydroxyl-terminated silicone oil is mixed in anhydrous tetrahydrofuran, cooled in an ice-water bath, and then divinyldichlorosilane is slowly added. After that, the ice-water bath is removed and triethylamine is added to carry out a substitution reaction to prepare an alkenylated polysiloxane intermediate. Step A2: Dissolve benzoin dimethyl ether in acetone, then add alkenylated polysiloxane intermediate and polyethylene glycol monomethyl ether mercapto group under nitrogen protection and mix well. Carry out an addition reaction under ultraviolet irradiation at room temperature to prepare a bending stabilizer.

2. The bend-resistant data cable sheath according to claim 1, characterized in that, The molar ratio of the hydroxyl content of divinyldichlorosilane and hydroxyl-terminated silicone oil is 1:2.2-2.4, and the amount of triethylamine used is 10-18 wt% of the weight of both.

3. The bend-resistant data cable sheath according to claim 2, characterized in that, The average molecular weight of hydroxyl-terminated silicone oil is 2000-3000.

4. The bend-resistant data cable sheath according to claim 3, characterized in that, The molar ratio of thiol groups in the vinyl group of the alkenylated polysiloxane intermediate to the thiol group of polyethylene glycol monomethyl ether is 1:1.05-1.1, and the benzoin dimethyl ether is 0.05-0.07 wt% of the total amount of both.

5. A bend-resistant data cable sheath according to claim 4, characterized in that, The average molecular weight of polyethylene glycol monomethyl ether thiol is 500-1000.

6. The bend-resistant data cable sheath according to claim 5, characterized in that, Ultraviolet radiation intensity is 25-35 mW / cm 2 .

7. A bend-resistant data cable sheath according to claim 6, characterized in that, The bending stabilizer accounts for 5.5-9.2 wt% of the sheath components.

8. A method for preparing a bend-resistant data cable sheath according to any one of claims 1-7, characterized in that, Specifically, liquid silicone rubber, bending stabilizer and additives are mixed evenly, and the mixture is then injection molded, demolded and vulcanized to obtain a bending-resistant data cable sheath.

9. The method for preparing a bend-resistant data cable sheath according to claim 8, characterized in that, The injection molding temperature is 160-170℃, the injection pressure is 40-45MPa, and the vulcanization molding temperature is 200-220℃.